Probing Biosystems by Vibrational Spectroscopy: From Human Cells to Bones - Marques, Maria Paula M. (My University, 2022)
The research activity of the R&D Group Molecular Physical-Chemistry of the University of Coimbra, Portugal (http://www.ci.uc.pt/qfm/ ), is focused on studies of biosystems by vibrational spectroscopy, from optical methods (Raman and infrared) to neutron scattering techniques (inelastic and quasi-elastic) – to yield both structural/conformational and dynamical information. The present lecture reports results on: (i) the impact of novel Pt- and Pd-anticancer agents on human cancer cells – aiming at evaluating their efficacy and identifying new therapeutic targets (ii) the normal-to-cancer transition, probing tissues resected from human patients (both tumour and non-malignant) – in order to allow a more accurate and early cancer diagnosis (iii) the effect of heat on human bones – for future applications in Forensic Science and Archaeology
Keywords: Espectros de vibración; Sistemas biológicos; Vibrational Spectroscopy; Human Cells; Probing biosystems